Familial Aggregation of a Novel Missense Variant of COL2A1 Gene Associated with Short Extremities: Case Report and Review of the Literature - Panagiotis Christopoulos; Anna Eleftheriades; George Paltoglou; Eleni Paschalidou; Emmanouil Kalampokas; Lina Florentin; Chrysanthi Billi; Makarios Eleftheriades (MDPI AG, 2022)
We present two cases of family members (first cousins) with short extremities caused by a novel variant of COL2A1 gene (NM_001844.5). Case 1 description: A 29-year-old woman presented in her first pregnancy for a second trimester anomaly scan at 23 weeks of gestation. Fetal long bones were measured below the third centile for gestational age. Follow-up scans revealed fetal long bone growth deceleration. Initial genetic work-up was negative and the rest of the maternal follow-up was unremarkable. A male baby weighing 3180 g was delivered at 39 weeks and 4 days of gestation. Case 2 description: A 33-year-old pregnant woman presented for a routine second trimester anomaly scan at 20 weeks and 4 days of gestation. All fetal measurements were appropriate for the gestational age. The routine growth scan performed at 32 weeks showed fetal long bone measurements below the third centile for gestational age, while the follow-up growth scan at 36 weeks and 4 days of gestation revealed consistent, below the third centile, fetal long bone growth. Given that the fetuses of these two cases were related (first cousins), whole exome sequencing (WES) was performed on Case 2. WES revealed a novel heterozygous missense variant c.1132G>A (p. Gly378Ser) of COL2A1 gene (NM_001844.5). Subsequently, targeted genetic sequencing for the variant was performed on Case 1 and the same novel variant was found. Targeted sequencing revealed the same variant in the mother of Case 1 and the father of Case 2 (siblings). A female baby weighing 3200 g was delivered at 40 weeks and 4 days of gestation.